Evolutionary diversifications of plants on the Qinghai-Tibetan Plateau - Wen, Jun; Zhang, Jianqiang; Nie, Ze-Long; Zhong, Yang; Sun, Hang (Frontiers in Genetics, 2014)
The Qinghai-Tibetan Plateau (QTP) is the highest and one of the most extensive plateaus in the world. Phylogenetic, phylogeographic and ecological studies support plant diversifications on the QTP through multiple mechanisms such as allopatric speciation via geographic isolation, climatic oscillations and divergences, pollinator-mediated isolation, diploid hybridization and introgression, and allopolyploidy. These mechanisms have driven spectacular radiations and/or species diversifications in various groups of plants such as Pedicularis L., Saussurea DC., Rhododendron L., Primula L., Meconopsis Vig., Rhodiola L., and many lineages of gymnosperms. Nevertheless, much work is needed toward understanding the evolutionary mechanisms of plant diversifications on the QTP. Well-sampled biogeographic analyses of the QTP plants in the broad framework of the Northern Hemisphere as well as the Southern Hemisphere are still relatively few and should be encouraged in the next decade. This paper reviews recent evidence from phylogenetic and biogeographic studies in plants, in the context of rapid radiations, mechanisms of species diversifications on the QTP, and the biogeographic significance of the QTP in the broader context of both the Northern and Southern Hemisphere biogeography. Integrative multidimensional analyses of phylogeny, morphological innovations, geography, ecology, development, species interactions and diversifications, and geology are needed and should shed insights into the patterns of evolutionary assembly and radiations in this fascinating region.